Implementation and Operational Research: Implementation of Multiple Point-of-Care Testing in 2 HIV Antiretroviral Treatment Clinics in South Africa. (1st February 2016) - Gous, Natasha M.; Scott, Lesley E.; Potgieter, Johan; Ntabeni, Lumka; Sanne, Ian; Stevens, Wendy S.
Abstract : Background: A plethora of point-of-care (POC) tests exist in the HIV and tuberculosis diagnostic pipeline which require rigorous evaluation to ensure performance in the field. The accuracy and feasibility of nurse-operated multidisciplinary-POC testing for HIV antiretroviral therapy (ART) initiation/monitoring was evaluated. Methods: Random HIV-positive adult patients presenting at 2 treatment clinics in South Africa for ART initiation/monitoring were consented and enrolled. POCT was performed by a dedicated nurse on a venipuncture specimen; Pima (CD4), HemoCue (hemoglobin), Reflotron (alanine aminotransferase, creatinine), Accutrend (lactate) and compared with laboratory testing. External quality assessment, training, workflow, and errors were assessed. Results: n = 324 enrolled at site1; n = 469 enrolled at site 2. Clinical data on n = 305 participants: 65% (n = 198) female with a mean age of 39.8 (21–61) years; mean age of males 43.2 (26–61) years; 70% of patients required 3 or more POC tests/visit. External quality assessment material was suitable for POCT. CD4, hemoglobin and alanine aminotransferase testing showed good agreement with predicate methodology; creatinine and lactate had increased variability. Pima CD4 misclassified up to 11.6% of patients at 500 cells per microliter and reported 4.3%–6% error rate. A dedicated nurse could perform POCT on 7 patients/day; inclusion of Pima CD4 increased time for testing from 6 to 110 minutes. Transcription error rate was 1%. Conclusions: Nurses can accurately perform multidisciplinary POCT for HIV ART initiation/monitoring. This will however, require a dedicated nurse as current duties will increase if POC is added to workflow. The use of Pima CD4 will increase patients initiated on ART. Connectivity will be central to ensure quality management of results, but overall impact will need to still be addressed.